Conservation et transformation du patrimoine vivant - Pierre-Marie Tricaud (Projets de Paysage)
This article goes back to the viva voce of a thesis which tackles the paradox of the conservation of a living heritage – not only in the biological sense of the term, but everything that is defined through time : landscape, city, intangible heritage, and, in one way or another, almost every kind of heritage. The living being changeable, even deadly, its conservation can be in conflict with its transmission, which is the true issue of any heritage : and one does not pass something on without transforming it. The jury’s reports, the account and the discussions during this viva were less interested in this overall position, upon which opinions seem to be divided, than on the terms of the implementation of this transmission-transformation – which were supposed to be developed in the last part of this thesis, from the four case studies (vineyards of the worldwide heritage, Loire Valley, roads, the Bièvre’s re-opening). Here are notably tackled the place of these case studies, the question of the disciplinary field, the definition of living heritage, the roles of the protagonists, and also the pertinence and the range of the notion of "re-employment" that the thesis offers.